Comparison of the Effectiveness of Dermapen Using Trambosit Plasma and Scar Serum Dermapen Actions on Scar Acne Areas on the Skin Surface of Wistar Female Rats (Rattus Norvegicus) - Riza Al Djoefri, Mohamad; Wienaldi, Wienaldi; Chailur, Muhammad; Marthin Simbolon, Boyke (Jurnal EduHealth, 2023)
This study aimed to analyze and compare the effectiveness of the action of dermapen using plasma from platelets with the movement of dermapen using scar serum on pockmarked areas on the skin surface of female Wistar rats (Rattus norvegicus). The results of wound observations based on the period (days) with an average healing time of 10.4 days and 12 days needed by each mouse to close the wound in the PRP dermapen group were faster than the serum scar group. This can be explained by the PRP content containing growth factors important for wound healing and tissue regeneration, thus accelerating healing. Meanwhile, scar serum contains concentrates that are useful for nourishing and moisturizing the skin, which can easily penetrate the deepest layers of the skin, thereby accelerating skin regeneration. Further microscopic studies, such as histopathological studies, are needed to examine the number of fibroblasts.